Pengaruh Perlakuan Alkali terhadap Sifat Tarik Bahan Komposit Serat Rami-Polyester - Kuncoro Diharjo (Institute of Research and Community Outreach, Petra Christian University, 2006)
The Natural Composite (NACO) is material that has a good potential to be developed in Indonesia. The mechanical bonding of the composite reinforced natural fiber can be increased by using chemical treatment of fiber or by using the addition of coupling agent. The chemical treatment, for example alkali treatment, is often used because it is more economic. The objective of this research is to investigate the effect of alkali treatment to the tensile properties of unidirectional continuous ramie fiber reinforced polyester composite. Visual inspections were performed to asses the mechanism of fracture. The ramie fiber was immersed in the alkali solution (5% NaOH for 0, 2, 4, and 6 hours. And then, it was washed using fresh water and dried naturally. The matrix used in this research is unsaturated polyester resin 157 BQTN with MEKPO hardener 1% (v/v). The composites were made by using press mold method for Vf